Улучшение энергетических характеристик параллельного резонансного инвертора - Афанасьев, А.М. (Технічна електродинаміка, 2012)
Based on the analysis of the known structures the new structure of high-frequency transistor generators for induction heating is synthesized. That structure combines the positive properties of methods of forming the output voltage in the resonant circuit. Using a simulation model the electromagnetic processes are investigated and the energy efficiency of the proposed structure of IGBT resonant inverter is analyzed.